Comparison between adverse effects of I/v Inj Labetalol Vs Inj Hydralazine during treatment of Hypertension in pregnancy - Muhammad Kamran Yousaf, Shazia Nourin, Sohail Bashir Sulehria, Nauman Dawood, Ali Asad Khan, Naeem Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To examine and compare side effects of intravenous Labetalol and Hydralazine in the treatment of Hypertension in pregnancy in developing countries like Pakistan. Methodology: A six-month randomised controlled experiment was undertaken at the Lady Aitchison Hospital's, Department of Obstetrics and Gynaecology. In the study, 330 individuals with severe hypertension who were between the ages of 20 and 35 years old and had been pregnant for more than 20 weeks were included. Patients were split into two groups of equal size. Group A was administered a 20mg IV bolus of Labetalol while Group B was administered a 5-10mg IV bolus of Hydralazine. The patients were monitored during the administration period of 60 minutes and all this data was entered into a proforma. Results: Females had an average age of 27.43±3.47 years and average gestational age in females was 28.98±4.49 weeks. The systolic blood pressure in all females was 109.43 ±16.93mmHg after 60 minutes of therapy, and mean diastolic blood pressure was 77.28±14.73mmHg. A total of 135(40.9%) women suffered from maternal hypotension [27(16.36%) with Labetalol vs 108(65.43%) with Hydralazine], and 55(16.68%) females exhibited abnormal fetal heart rate [1 (0.61%) with Labetalol and 54(32.72%) with Hydralazine]. Therefore, the Hydralazine adverse effect was statistically significant (p-value = 0.000). Practical Implication: If the results of this study are applied in clinical practice in patients of pregnancy induced hypertension, female patients ca be prevented of side effects of hydralazine by using labetalol to treat hypertension in pregnancy, so it is very beneficial for patients. Conclusion: The study concludes that use of Hydralazine in females with PIH should be discouraged, whereas the use of Labetalol should be encouraged in a developing country like Pakistan. Keywords: Pregnancy Induced Hypertension (PIH),Gestational Hypertension(GH), hypotension, headache, abnormal fetal heart rate, palpitation, tachycardia, intravenous.